Overexpression of mannitol-1-phosphate dehydrogenase increases mannitol production and confers salt and chilling tolerance in transgenic petunia cv. Mitchell - Jiang, Yu-Jen, author; Stushnoff, Cecil, advisor; Hughes, Harrison G., committee member; Ishimaru, Carol, committee member; Wallner, Stephen J., committee member (Colorado State University. Libraries, 2000)
Diploid petunia plants (Petunia hybrid, cv. Mitchell) transformed with a bacterial gene (mt/ D) encoding mannitol-1-phosphate dehydrogenase enzyme (MTL D), resulting in high mannitol expression, were developed and studied in this research. Transgenic lines and wild type control plants were exposed to salinity and chilling stress with the express goal of delineating the impact of manniol on these abiotic stresses. Phenotypically, there was no difference in growth between in vivo wild type and transgenic lines under non-stress conditions. However, transgenic lines expressing high mannitol levels were found to exhibit a greater capacity to tolerate salinity and chilling stresses compared to wild type and transgenic lines expressing low mannitol levels. Enhanced salinity tolerance was observed in seed germination (T2 generation), and in vegetative growth and floral development of transgenic lines expressing high mannitol levels. Also, based upon foliage symptoms and membrane leakage, transgenic lines expressing high mannitol levels were more tolerant of chilling stress compared to with wild type and transgenic lines expressing low mannitol levels. Carbohydrate analysis of wild type and transgenic plants showed that mannitol was the single carbohydrate most affected by plant lines. Two transgenic lines (M3 and M8) always had higher mannitol expression levels when compared to wild type and the other two transgenic lines (M2 and M9) under non-stress and stress conditions. Therefore, the function of high mannitol expression should be considered in developing improved tolerance of petunia plants to salinity and chilling stresses. However, assuming 90 % water content in leaf tissue, leaf osmotic potential of high mannitol expressing lines contributed by mannitol accounted for only 0.006 %-0.01 % of increased osmoregulation caused by salinity stress, and 0.04 %-0.06 % of the increase in osmotic potential caused by chilling stress, respectively. Quantitatively, mannitol appears not to play a role as an osmoregulator in osmotic adjustment in response to both salinity and chilling stresses. Rather, the data from this research suggest that mannitol may function as an important osmoprotectant in enhancing salt and chilling tolerance of those transgenic petunia lines expressing high mannitol levels.
Covers not scanned.
Keywords: Petunias; Plants -- Effect of cold on; Plants -- Effect of salt on